Kualitas Pelayanan Pajak Kendaraan Bermotor Di Upt Pengelolaan Pendapatan Samsat Kota Pekanbaru - Yolanda, Yolanda Irlin Saprianti (UIR Press, 2023)
The Government attempted to improve its performance in order to improve the quality of service to the community. Later, the government as a provider of services seeks to provide quality service in accordance with community expectation. Therefore the Riau provincial government in this case the Deprtement of Revenue of Riau provide excellent service and improve service and accordance with Act 25 of 2009. Then the establishment of joint offices units to facilitate the implementation of motor vehicle tax collection services. However, there are many public complaints about services available in the town office Pekanbaru units. Based on these problems, the researchers are interested in examining how the quality of public services in the annual motor vehicle tax validation. Concepts that researchers use the theory by Agus Dwiyanto there are several dimensions of services quality are : attitude officers, procedures, time, facilities, services. This research uses descriptive method with qualitative approach. Data obtained though interviews submitted to the informant and then analyzed by researchers. It also collected secondary data relating to the issues under investigation. Of the results of this study indicate that the quality of public services at the annual motor vehicle tax validation (study office Pekanbaru city) has not run optimally. There is a weakness-weakness concerning the quality of services such as : The lack of socialization to the community officers about the latest regulations to which they apply and the not fit punctuality in accordance with the existing standard operating procedures, still the tendency of officers to provide services that are not fair to the tax payers.